College Students Readiness Facing the Industrial Revolution 4.0 - Mortigor Afrizal Purba; Agus Defri Yando (Jurnal Mantik, 2020)
This research was conducted to analyze "the influence of the competence of undergraduate, government regulation, college policy, and professional ethics on the ability of undergraduate in facing the era of industrial revolution 4.0". The samples in this study were Accounting Graduates of the Faculty of Economics and Business, Universitas Putera Batam, Universitas International Batam, Universitas Batam, and Universitas Riau Kepulauan. The analytical method used is Multiple Linear Regression with SPSS 22 For Windows software. Based on the results of simultaneous hypothesis testing shows that simultaneously the competencies of undergraduate accounting, government regulation, college policy and professional ethics affect the ability of undergraduate accounting to compete in the era of industrial revolution 4.0. Partially, it shows that the competencies of undergraduate accounting, government regulation, college policy, and professional ethics influence the ability of accounting graduates to compete in the face of the 4.0 industrial revolution era